Multistring five-level inverter with novel PWM control scheme for PV application - Rahim, N.A.; Selvaraj, J. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
This paper presents a single-phase multistring five-level photovoltaic (PV) inverter topology for grid-connected PV systems with a novel pulsewidth-modulated (PWM) control scheme. Three PV strings are cascaded together in parallel configuration and connected to a five-level inverter to produce output voltage in five levels: zero, +1/2V(dc), V(dc), -1/2V(dc), and -V(dc). Two reference signals that were identical to each other with an offset that was equivalent to the amplitude of the triangular carrier signal were used to generate PWM signals for the switches. DSP TMS320F2812 is used to implement this PWM switching scheme together with a digital proportional-integral current control algorithm. The inverter offers much less total harmonic distortion and can operate at near-unity power factor. The validity of the proposed inverter is verified through simulation and implemented in a prototype. The experimental results are compared with a conventional single-phase multistring three-level grid-connected PWM inverter.